A concepção de história na ficção de Ana Miranda - Thiago, Diovana Ferreira de Oliveira (2014)
This dissertation investigates the concept of history in Ana Miranda‘s work, in order to demonstrate how she invents a colony in her novels and how an image of colonial times was being drawn in her fiction throughout her literary trail. Such image converges with an important moment in our history - the historiographical renewal from the 80s. In this sense, it is essential to demonstrate the place that women occupy in this portrait of the colony that the author presents. The woman who arises in Ana Miranda‘s fiction is not restricted to the domestic space and the roles of submission. This woman invades the public space, transgresses the rules, consciously conquers and takes an active role as subject of her own history, gaining visibility and subverting myths and stereotypes.